Assessment of adherence to preventive treatment of plaque-induced oral diseases using sugar-free gums: a controlled clinical trial - María Cecilia Martínez-Pabón; Carolina Mesa-Arango; Cecilia María Martínez-Delgado; María Isabel Pérez-Cano; Diana María Isaza-Guzmán; Sergio Iván Tobón-Arroyave (Universidad de Antioquia, 2019)
Introduction: the aim of this study was to assess the adherence to a preventive treatment of plaque-induced oral diseases using two sugar-free gums, establishing their effect on cariogenic bacteria counts as abiological marker of treatment response. Methods: a double-blind, randomized, parallel-group, controlled intervention study was conducted in 96 young adult university students in an experimental period of 30 days. Participants were distributed into two groups and given a chewing gum with either pentitol or hexitol + CPP-ACP complex to be taken three times a day for 20 minutes after conventional oral hygiene. Saliva samples were collected at baseline to evaluate counts of Streptococcus mutans (SM) and Lactobacillus spp. A survey was conducted at the end of the experimental period to assess the levels of adherence to treatment, remeasuring bacterial counts. Results: SM counts showed statistically significant differences between the study groups at the end of the experimental period, with a decreasing tendency in both groups. Intragroup difference was observed in patients who took pentitol gum with a marked reduction in SM counts. Conclusion: the final estimate of adherence to treatment showed that the type of chewing gum patients were given had no influence and therefore such gums can be used, considering the therapeutic agents that most contribute to patient's particular case and preferences.